Bone transport with unilateral external fixator for humeral defect reconstruction: a retrospective analysis of post-traumatic osteomyelitis - Hamiti, Yimurang; Abudureyimu, Patiman; Lyu, Gang; Yusufu, Aihemaitijiang; Yushan, Maimaiaili (Frontiers in Surgery, 2025)
BackgroundLarge humeral defects resulting from post-traumatic osteomyelitis present significant challenges in orthopedic reconstruction. This study evaluates the efficacy of bone transport using a unilateral external fixator for treating such defects.MethodsA retrospective analysis was conducted on 15 patients (9 males, 6 females; mean age 29.3 ± 11.7 years) with humeral defects due to post-traumatic osteomyelitis, treated between January 2017 and January 2021. The mean defect size was 7.2 ± 1.4 cm (range, 5.3–9.8 cm). All patients underwent bone transport using a unilateral external fixator. Primary outcomes included external fixation time (EFT), external fixation index (EFI), and bone healing time. Secondary outcomes comprised ASAMI bone and functional scores, DASH scores, range of motion, and complications.ResultsThe mean EFT was 342.5 ± 35.6 days (range, 290–410 days), and the mean EFI was 47.5 ± 3.8 days/cm (range, 42–54 days/cm). Bone union was achieved in all cases, with a mean healing time of 11.4 ± 1.2 months (range, 9.5–13.5 months). ASAMI bone results were excellent in 10 patients (66.7%) and good in 4 (26.7%). ASAMI functional results showed excellent outcomes in 8 patients (53.3%) and good in 5 (33.3%). The mean DASH score improved significantly from 35.2 ± 3.6 preoperatively to 15.5 ± 3.2 at final follow-up (P < 0.001). Complications occurred in 7 patients (46.7%), with pin site infections being the most common (26.7%).ConclusionBone transport using a unilateral external fixator demonstrates efficacy in treating large humeral defects due to post-traumatic osteomyelitis, yielding good to excellent bone and functional outcomes with manageable complications. These findings extend previous research, highlighting the technique's efficacy in achieving both bone union and functional restoration. This approach deserves consideration as a primary treatment option for complex humeral reconstruction cases, particularly when traditional methods may be insufficient.